Targeting the Achilles Heel of FtsZ: The Interdomain Cleft - Pradhan, Pinkilata; Margolin, William; Beuria, Tushar Kant (Frontiers in Microbiology, 2021)
Widespread antimicrobial resistance among bacterial pathogens is a serious threat to public health. Thus, identification of new targets and development of new antibacterial agents are urgently needed. Although cell division is a major driver of bacterial colonization and pathogenesis, its targeting with antibacterial compounds is still in its infancy. FtsZ, a bacterial cytoskeletal homolog of eukaryotic tubulin, plays a highly conserved and foundational role in cell division and has been the primary focus of research on small molecule cell division inhibitors. FtsZ contains two drug-binding pockets: the GTP binding site situated at the interface between polymeric subunits, and the inter-domain cleft (IDC), located between the N-terminal and C-terminal segments of the core globular domain of FtsZ. The majority of anti-FtsZ molecules bind to the IDC. Compounds that bind instead to the GTP binding site are much less useful as potential antimicrobial therapeutics because they are often cytotoxic to mammalian cells, due to the high sequence similarity between the GTP binding sites of FtsZ and tubulin. Fortunately, the IDC has much less sequence and structural similarity with tubulin, making it a better potential target for drugs that are less toxic to humans. Over the last decade, a large number of natural and synthetic IDC inhibitors have been identified. Here we outline the molecular structure of IDC in detail and discuss how it has become a crucial target for broad spectrum and species-specific antibacterial agents. We also outline the drugs that bind to the IDC and their modes of action.